Cultivating the Future: Analyzing the Adoption Extent and Adoption Factors of Technology Among Agriculture MSMEs in Pamijahan, Bogor Regency - Widjanarko, Moreno Verli; Harahap, Fahrur Rozi; Frans, Frans; Cahyadi, Eko Ruddy (Peneliti.net, 2024)
The rapid evolution of agricultural technology offers unique opportunities and challenges, particularly for micro, small, and medium enterprises (MSMEs) in the food crop sector. This study investigates the adoption of agricultural technology among rice farmers in Pamijahan, an area pivotal for rice production in Bogor Regency. The study's objectives are to analyze the extent and factors influencing agricultural technology adoption among rice farmers in Pamijahan. The methodological approach begins with cross-tabulation to analyze the extent of technology adoption across various processes in the agribusiness management system and followed by multiple linear regression analysis based on the simplified Technology Acceptance Model (TAM), integrating variables such as perceived usefulness, ease of use, and attitudinal tendencies. Data were gathered over a period of five months. Primary data collection involved structured questionnaires targeted at rice farmers, while secondary data was obtained from institutional reports. The results reveal a moderate adoption level, with significant use of staple seed, hand tractor, and simple grinding technologies, but a persistent reliance on manual methods for planting and harvesting. The TAM analysis shows that perceived usefulness, ease of use, and attitudes towards technology are key influencers of adoption, accounting for 67.7% of the variance in farmers' intention to use technology. These findings underscore the importance of farmers' perceptions of technology adoption and suggest that improving technology understanding and accessibility could significantly enhance adoption rates, promoting agricultural productivity and sustainability in smallholder farming.